Non-selective non-steroidal anti-inflammatory drugs (NSAIDs) and cardiovascular risk - Fanelli, Andrea; Romualdi, Patrizia; Vigano', Roberto; Lora Aprile, Pierangelo; Gensini, Gianfranco; Fanelli, Guido (Acta Biomedica Atenei Parmensis, 2013)
NSAIDs are largely used for the treatment of a huge variety of clinical conditions in order to relieve symptoms related to inflammation.The use of NSAIDs is associated with a potential increased risk of gastrointestinal and cardiovascular complications.The cardiovascular risk related to NSAIDs administration is often underestimated and it is frequently believed to be less important than the gastrointestinal risk. Adverse effects of NSAIDs are specifically related to their underlying mechanisms of action.The most plausible mechanism underlying the cardiovascular risk of NSAIDs has been identified in the profound inhibition of COX-2-dependent PGI2 in the presence of incomplete and intermittent inhibition of platelet COX-1. Nevertheless, the cardiovascular risk related to the use of NSAIDs is not only due to the COX-2 selectivity. An important determinant of the clinical effects of NSAIDs depends on the pharmacokinetic features of the different drugs such as half-life, and type of formulations, which can influence the extent and duration of patient exposure to COXisozyme inhibition. The aim of this review is to analyse the mechanisms behind the cardiovascular risk of different NSAIDs.